The Effect of Transactional Leadership, Transformational Leadership, Creative Self Efficacy on Innovative Work Behavior and Employee Performance Moderated by Digital Literacy - Effiyaldi, Effiyaldi; Mulyono, Herry; Suratno, Eddy; Pasaribu, Johni Paul Karolus (Universitas Brawijaya, Indonesia, 2024)
Innovative Work Behavior and Employee Performance moderated by Digital Literacy has many benefits. To get these benefits, it is necessary to have the roles that supports the creation of Innovative Work Behavior and Employee Performance moderated by Digital Literacy. The purpose of this study is to build an understanding of the roles of Transactional Leadership, Transformational Leadership, Creative Self-efficacy In Innovative Work Behavior and Employee Performance moderated by Digital Literacy. The nature of this study is explanatory research.Data collection through questionnaire.The sampling method was target sampling. The sample size was 250 SME employees in Jambi city, and structural equation modeling (SEM) with his AMOS software was used for data analysis. The results of this study suggest that Transactional Leadership, Transformational Leadership, Creative Self -efficacy has a significant effect on Innovative Work Behavior and on Employee Performance. Digital Literacy strengthens the link between Innovative Work Behavior and Employee Performance. From the data it is recommended to increase the Transactional Leadership, Transformational Leadership, Creative Self-efficacy, and Digital Literacy to Improve the Innovative Work Behavior and Employee Performance.